Tanggap Pertumbuhan dan Produksi Tembakau Deli (Nicotiana tabacum L.) terhadap Pemberian Vermikompos pada Beberapa Tingkat Pemberian Air - Ahmad Fadli; Irsal Irsal; Eva Sartini Bayu (Jurnal Agroekoteknologi, 2014)
Deli tobacco is one of the leading agricultural commodity in North Sumatera . Water availablity andorganic material is very important aspect that influence quality of tobacco leaf. For that purposethis research aimed to know response growth and yield of Deli tobacco by giving vermicompost onwater treatments. This research was conducted in Green House of Agricalture Faculty University ofnorth sumatera in November 2013 – January 2014 using a randomized block design with twofactors and three replications. The first factor is vermicompost giving (control, 10%, 20% and30%). The second factor is water treatments (100%, 75%, 50% and 25%). Parameter observed wereplant height, numbers of leaf, stem of diameter, long leaves sand, 1 foot long leaves,leaf widthsand, 1 foot wide leaves, thick leaf sand, 1 foot thick leaves, summarize of leaf area, greennes ofleaf, root length, plant dry weight, water use efficiency.The results showed that vermicompostgiving significantly effect stem of diameter 18 days after transplanting. Water treatments showsincreasing effect stem of diameter 46 days after transplanting, long leaves sand, leaf width sand,thick leaf sand and water use efficiency.Keywords : vermicompost, water treatments, Deli tobacco